PENGGUNAAN MODEL PEMBELAJARAN PORTOFOLIO DALAM UPAYA MENUMBUHKAN KONSEP DIRI DAN KREATIVITAS PESERTA DIDIK - Sadanah Sadanah; Pargito Pargito; Eddy Purnomo (Faculty of Teacher Training and Education, University of Lampung, 2013)
Abstract. This was a classroom action research, conducted to develop students’ self-concept and creativity, strength and weaknesses of teachers and students in learning process. The research result showed that (1) portfolio learning model can develop students’ self-concept (2) portfolio learning model can develop students’ creativity. In cycle I, 9 or 27% of students have high self-concept category and the average score was 68%. In cycle II showed an increase in which 12 students or 35% of students have high self-concept category and average score was 74% and the students’ development of self-concept increased in cycle III with 27 students or 79%, with average score 77%. The development of students’ creativity in cycle I was 20 students or 59% with medium category with average score 64%, cycle II showed the growth, that was 24 students or 71% had already got medium category of creativity and average score was 67% and cycle III students that got development of creativity were 29 students or 85%, with high category from entire students in which 34 students with average score 75%. Thus, it can be concluded that portfolio learning model can develop students self-concept and creativity.Keywords: portfolio learning model, self-concept, creativity